Pharmacoepigenomics of Replication Timing: How Anti- Cancer Drugs Reshape Chromatin Domains and Mutational Landscapes. - Atul Khajuria; Ashish Kumar (International Journal of Molecular Biotechnological Research, 2026)
DNA replication timing serves as a fundamental epigenetic feature that organizes genome function during the cell cycle (3), while anti-cancer drugs profoundly alter this process to disrupt tumor growth(4). These agents target chromatin architecture, shifting replication domains and reshaping mutational patterns critical for cancer evolution (1,5). DNA replication timing (RT) domains serve as dynamic epigenetic organizers, partitioning the genome into early- and late-replicating regions that correlate with chromatin states, gene activity, and mutational vulnerability in cancer. Anti-cancer drugs, including chemotherapeutic agents like platinum compounds, alkylators, and epigenetic modulators (e.g., HDAC inhibitors, DNA methyltransferase inhibitors), profoundly reprogram RT programs, inducing shifts from stable early- replicating euchromatin to delayed late-replicating heterochromatin enriched in H3K27me3 and hypomethylated CpG islands. This pharmacoepigenomic rewiring disrupts topologically associating domains (TADs), promotes long-range chromatin interactions, and elevates replication stress, fostering double-strand breaks preferentially in late-replicating loci prone to facultative heterochromatin transitions. Emerging evidence reveals that such RT alterations underpin therapy-induced mutational landscapes, with early-replicating regions susceptible to translocations due to heightened transcription-replication conflicts, while late-replicating zones accumulate kataegis-like signatures from APOBEC hyperactivity and error- prone repair. In preclinical models and survivor cohorts, adolescent chemotherapy exposure imprints persistent sperm epimutations—differentially methylated regions (DMRs) in CpG deserts—suggesting intergenerational inheritance of altered RT domains that may predispose offspring to genomic instability. Clinical pharmacoepigenomic profiling, integrating Repli-seq, ATAC-seq, and whole-genome bisulfite sequencing, demonstrates that RT shifts predict therapy response and relapse, as seen in breast and prostate cancers where late-RT domains correlate with aggressive epigenomic deregulation.
Keywords: anticancer drugs; chromatin domains; mutational landscapes; pharmacoepigenomics; replication timing